Identification and structural analysis of novel malathion-specific DNA aptameric sensors designed for food testing. (August 2022) - Kadam, Ulhas Sopanrao; Trinh, Kien Hong; Kumar, Vikas; Lee, Keun Woo; Cho, Yuhan; Can, Mai-Huong Thi; Lee, Hyebi; Kim, Yujeong; Kim, Sundong; Kang, Jaehee; Kim, Jae-Yean; Chung, Woo Sik; et al.
Abstract: Malathion is an organophosphate chemical (OPC) and a toxic contaminant that adversely impacts food quality, human health, biodiversity, and the environment. Due to its small size and unavailability of sensitive sensors, detection of malathion remains a challenging task. Often chromatographic methods employed to analyze OPCs suffer from several shortcomings, including cost, immobility, laboriousness, and unsuitability for point-of-care settings. Hence, developing a specific and sensitive diagnostic sensor for quick and inexpensive food testing is essential. We discovered four unique malathion-specific ssDNA aptamers; designed two independent sensing strategies using fluorescence labeling and Thioflavin T (ThT) displacement. Selected aptamers formed the G4-quadruplex-like (G4Q) structure, which helped develop a label-free detection approach with a 2.01 ppb limit of detection. Additionally, 3D structures of aptamers were generated and validated using a series of computational modeling programs. Furthermore, we explored structural features using CD spectroscopy and molecular docking, probing ligands' binding mode, and revealed vital intermolecular interactions with aptamers. Subsequently, the novel sensors were optimized to detect malathion from food samples. The novel sensors could be further developed to meet the demands of sensing and quantifying toxic contaminants from real food samples in field conditions. Graphical abstract: Image 1 Highlights: Discovered 'four' unique ssDNA aptamers specific to malathion. Designed and developed malathion-specific novel G4-quadruplex aptameric biosensors. Demonstrated two independent detection strategies using fluorescence labeling and label-free. displayed high affinity ( Kd values) and achieved ultrasensitive detection of 2.01 ppb. Explored molecular interactions and binding pocket of targets using CD spectroscopy, molecular modeling, and docking.